A MIDDLE ENGLISH TEXT REVISED BY A RENAISSANCE READER: JOHN WOTTON'S ANNOTATIONS TO BRITISH LIBRARY MS SLOANE 249 (FF. 180V-205) - Rodríguez Álvarez, Alicia; Domínguez Rodríguez, Mª Victoria (International Journal of English Studies, 2009)
BL MS Sloane 249 ff. 180v-205v is a fifteenth-century gynaecological treatise in the tradition of Gilbertus Anglicus' Compendium medicinae, classified by Green as Sickness of Women 2 (Green, 1992: 81-82). Unlike other Middle English gynaecological treatises, the text of this manuscript is thoroughly glossed by his Renaissance owner, one Jolin Wotton, MD (Green, 2003: 383), who considered its language obsolete and unusual. His annotations, which include corrections, additions, eliminations, substitutions, etc. slied light on the changing vocabulary, morphology, grammatical constructions and even on stylistic preferences. The aim of this paper is to classify and comment on these annotations and to stress their importance for the Historians of the English language.